2016
DOI: 10.14419/ijbr.v4i2.6281
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of best naringinase producing fungus isolated from the citrus fruits

Abstract: Naringinase enzyme has potential application in food and pharmaceutical industry. Naringin and limonin are principle bitter components in the citrus fruit. The microorganisms that associate with citrus fruit may have the ability to degrade the naringin by extracellular naringinase enzymes that are produced by microorganisms. The objective of the study is to isolate naringinase producing fungus from the citrus fruit to debitter the citrus juice and to characeterize the fungus. Citrus fruits were allowed to spoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The range of pH stability is generally from 4 to 8 [45,50,51]. In 2016, Srikantha et al [52] reached an activity as high as 449.58 U/g of dry matter in solid state fermentation for Aspergillus flavus. Some studies focused on the capacity of bacteria to produce naringinases, such as Bacillus spp.…”
Section: Naringinmentioning
confidence: 99%
“…The range of pH stability is generally from 4 to 8 [45,50,51]. In 2016, Srikantha et al [52] reached an activity as high as 449.58 U/g of dry matter in solid state fermentation for Aspergillus flavus. Some studies focused on the capacity of bacteria to produce naringinases, such as Bacillus spp.…”
Section: Naringinmentioning
confidence: 99%
“…Under the effect of optimized conditions, the loading capacity was found to increase by as high as 28 folds. In another study, Srikantha et al [18] utilized paddy husk and five different strains of fungi to screen their potential to produce the enzyme naringinase. The study reported that the strain Aspergillus flavus produced the maximum (highest) amount of enzyme among the compared strains of fungi.…”
Section: Microbial Sources and Production Of Naringinasementioning
confidence: 99%